Euthanasia at the Crossroads of Faith and Philosophy: Islamic vs. Western Thought: Eutanasia dalam Perspektif Agama dan Filsafat: Analisis Komparatif antara Pemikiran Islam dan Barat - Rahmani, Parwana (Lex Renaissance, 2025)
This article examines the perspectives of Islam and Western philosophy on euthanasia, focusing on whether it is acceptable within Muslim contexts. To provide a comprehensive understanding, the study employs an Islamic jurisprudential approach combined with analytical and descriptive methods. Drawing on primary Islamic sources, including the Qur’an, Hadith, scholarly fatwas, and Islamic ethical principles. The findings indicate that, due to the sanctity of human life as a divine gift, active euthanasia is strictly prohibited in Islam. However, in circumstances where medical treatment proves ineffective or futile, Islamic teachings permit the withdrawal or discontinuation of life-sustaining interventions.